Identificación de factores familiares que determinan la desición de compra de productos lácteos en el cantón Salcedo. - Palacios Galarza, Luis Alejandro (2018)
The present reseach has for aim identify the familiar factors which determine the decision to purchase lacteal products in the salcedo town, into the problem that was identified was the ignorance of familiar factors in the population, it is inquired the theoretical bases that support the information, about the familiar factors that affect in the decision to purchase lacteals products customers, obtaining relevant information about consumer behavior, the purchase decision and the process that consumers perform at the moment to decide what they will acquire. The analysis was based on quantitative research, for the statistical study was used the SPSS program, to do the lifting of the information was modidied a survey an invetigation of the authors Bravo, Fraj & Martínez, to the same extracted the questions that helped identify the familiar factors of purchase decision. The results obtained from the research tried to find the fundamental reasons that the consumer Salcedence pursues to buy the family consumption products, It has been made a relationship between the questions through dynamic tables for general a reliability in the information that was obtained with the survey application, through analysis, it was possible to determine which are the most relevant factors that the population considers when decide their purchase.